Aplikasi Edit Foto Background Dengan Menggunakan Metode K-Means Clustering - Ihsan Lubis; Herlina Andriani Simamora; Sayuti Rahman; Rosyidah Siregar; Husni Lubis (Program Studi Sistem Informasi, 2019)
Background photos become one of the most important things in every human activity. Where each background color contains its own meaning, depending on when the conditions where we use the background color. The background color is indispensable in the interests of humans in all matters relating to administration, for example, in the scope of work, school, and others. The background color change can be done by clustering the image. The initial stage done in changing the background color is to cluster the image first so that the background object can be found. In this study, the authors apply the k-means method to divide the objects into several parts. In this application before changing the background color we have to determine the number of clusters first, then the background color is changed according to the desired cluster. This application is designed using Matlab version 2010a. Test results ten images can be concluded that the success of background color changes can be done with a background that has one color while the background that has different colors can not change.Keywords: Image, Background, K-means, Clustering, Processing Image, Matlab 2010a